Analisis Diminutiv -chen Dan -lein Berbantuan Korpus Dalam Dongeng Karya Bruder Grimm - Munggaran, Heri Septian; Sudarmaji, Sudarmaji (Ideguru: Jurnal Karya Ilmiah Guru, 2026)
This study is motivated by the limited number of corpus-assisted studies on the use of the diminutive suffixes -chen and -lein in German literary texts, particularly in the fairy tales of Brüder Grimm. The study aims to describe the frequency, contexts of use, and semantic-pragmatic functions of diminutives in a fairy-tale corpus. This research employed a qualitative approach using a corpus-assisted content analysis design on 200 digital fairy tales analyzed with the AntConc software. The data consisted of words containing the suffixes -chen and -lein, which were analyzed based on frequency, collocation, contextual distribution, and connotative meaning. The findings revealed 524 occurrences of the suffix -chen and 112 occurrences of the suffix -lein. The suffix -chen was more dominant and tended to express affective nuances such as intimacy, tenderness, and empathy, whereas -lein was more limited in use and relatively emotionally neutral. The use of diminutives contributed to characterization, narrative atmosphere, symbolism, and emotional closeness between readers and characters. The study concludes that diminutives in fairy tales function not only morphologically but also as stylistic and pragmatic devices. These findings contribute to corpus linguistics and literary stylistics and open opportunities for comparative studies across genres and languages.